The Association between Serum Nesfatin-1 level and BMI in Iraqi patients with Polycystic Ovary Syndrome (PCOS) - Eham Amer Ali; Walaa Ahmed AL-Jedda; Shatha M.J AL-Khateeb; Abdilkarim Y. AL-Samarriae (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: to evaluate the nesfatin-1 levels in addition to other metabolic components in polycystic ovarysyndrome PCOS in a state that to be associated with both functions of ovary and obesity.Methods: A cross-section observational study was carried on total of forty-five (45) women in thereproductive age with polycystic ovary syndrome (23 obese, 22 non-obese) attending Infertility unit andoutpatients clinic of Gynecology and Obstetrics at AL-Yarmouk Teaching Hospital, in addition to forty (40)(30 obese, 10 non-obese) age matched healthy individuals. Serum nesfatin-1, TC, TG, HDL-C, FPG, FPI,E2, TT, LH, FSH and Prol were measured, in addition to HOMA-IR, BMI and LDL-C was calculated.Results: FPG (5.1±0.3 mmol/L), HOMA-IR (2.8±1.1) were significantly higher in PCOS group than theirresults in the control group (4.8±0.2 mmol/L), (2.2±1.3) (P ? 0.05, 0.01) respectively. Nesfatin-1 level(11.1±3.5 ng/ml), TT (1.7±0.3 pg/ml) and LH (6.5±2.8 mIU/ml) in PCOS group were significantly difference(P ? 0.001, 0.05) respectively, when compared their concentration in the control group (6.3±3.0 ng/ml),(0.9±o.1 pg/ml), (4.9±1.5 mIU/ml). Among the patients with PCOS, a strong positive correlation were foundbetween nesfatin-1 and WC (r=0.221 , P ? 0.05) , BMI ( r=0.267 , P ? 0.001), TT (r=0.218, P ?0.001), LH(r=0.263 , P? 0.001), IR (r=0.453 , P ? 0.001), FBG (r=0.257 , P ? 0.01), LDL-C (r=0.228 , P ? 0.05) andTG (r=0.223 , P ? 0.05). Besides that, a positive association were between HOMA-IR and BMI (r=0.460, P? 0.01), WC (r=0.429, P ?0.001).Conclusion: nesfatin-1 gives the impression to play an important action to regulate food intake and energyhomeostasis with a strong positive correlation with WC, BMI, IR, LDL-C and TG.